Nilai-Nilai Pendidikan Karakter dalam Peristiwa Isra Mikraj Perspektif Al Qur’an Dan Hadis Sahih - Miftahus Surur (Ambarsa : Jurnal Pendidikan Islam, 2022)
Telling story is one of the most effective learning methods. Stories are very interesting to listen and the lessons can deeply penetrate into the soul. Therefore, the Qur'an encourages Islamic people to take lessons from the stories of the previous people in the pass, as in Yusuf verse 111. Likewise, stories based on historical events of the Prophet Muhammad ﷺ, such as the story of Isra’ Mi’raj. The Isra’ Mi’raj event contains various lessons about good values ​​and good character that are very important for character education for Muslims. This study aims to describe the good values ​​of character education contained in the Isra’ Mi’raj event in a review of the Qur'an and Sahih Hadith. The type of research used in this study is library research with an interpretive approach and a historical research approach along with content analysis as the analysis technique. The data was obtained from the literature on the interpretation of the Qur'an and Sahih Hadith. This research is library research with an interpretive approach and a historical research approach along with content analysis as the analysis technique. The data is obtained from the literature on the interpretation of the Qur'an and Sahih Hadith. The Qur'an describes the events of Isra’ Mi’raj in outline, while the Hadith describes it in detail in the frame of a story according to the chronology of events experienced by the Prophet. Isra is the journey of Prophet Muhammad ﷺ from Masjid al Haram to Masjid al Aqṣa at night.